Покращений алгоритм призначення для планувальників завдань в неоднорідних розподілених обчислювальних системах - Sergiyenko, Anatolij M.; Simonenko, Valery P.; Simonenko, A. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2016)
The basics of designing the spatial schedulers are considered which are used in global heterogeneous GRID-systems. Several theorems are proven, which consider the bipartite graphs of task requests and resource relations. These theorems help to reduce the number of decision options by removing the unpromising elements in the adjacency matrix. This reduces the time complexity of the Hungarian algorithm from O(n3) to O(n1,5 log n). This approach is used in the adaptive multianalysis algorithm, which is based on a preliminary analysis and correction of the bipartite graph matrix. Its application to the matrices, which are filled to less than 30% of their volume, the scheduling algorithm has the statistical time complexity, which is close to linear.